PENGARUH PERAWATAN PAYUDARA TERHADAP KELANCARAN PRODUKSI ASI PADA IBU POSTPARTUM DI PUSKESMAS KASSI-KASSI, MAKASSAR - Sitti Mukarramah; Siti Surya Indah Nurdin; Zul Fikar Ahmad (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
Breast Milk is an essential intake containing complete nutrition required for infant growth and health. Its protein is much higher than formula milk. One of the methods to improve breast milk production is Breast care. Breast care is helpful for the reflex of the release and increasing the volume of breast milk. This study aimed to determine the effect of breast care on milk production on postpartum mothers at Kassi-Kassi Health Center Makassar. The study applied